MAXIMIZING THE POTENTIAL OF IBRUTINIB: MULTI-FACTOR OPTIMIZATION AND INTERACTION ANALYSIS FOR IMPROVED NANOBUBBLE FORMULATION AND BIOAVAILABILITY PERFORMANCE - LAXMI, B. VIJAYA; BHIKSHAPATHI, D. V. R. N.; RAJESHAM, V. V.; POORNIMA, P.; SANDHYA, P.; ARJUN, G. (International Journal of Applied Pharmaceutics, 2025)
Objective: Ibrutinib (IBR), a v-Raf murine sarcoma viral oncogene homolog B1 (BRAF) inhibitor, faces solubility challenges as a Biopharmaceutics Classification System Class II drug. The objective of this was to formulate IBR-loaded polylactic-co-glycolic acid (PLGA) nanobubbles (NBs) using the solvent evaporation method with ultrasound assistance. Methods: IBR-PLGA nanobubble optimization was achieved by implementing a four-factor, three-level BBD and a total of 29 experimental runs, including three replicated centre points, comprised the Box-Behnken design (BBD). The formulated NBs were characterized for particle size, zeta potential (ZP), drug entrapment efficiency (EE), compatibility studies in vitro studies, and stability studies along with in vivo studies in rats. Results: The optimized NBs displayed a particle size of 130±13.3 nm, ZP of-23.0±0.89 mV and EE of 49.14±1.32. In vitro studies revealed superior drug release (98%) with ultrasound versus plain drugs (20%). Fourier Transform Infrared Spectroscopy and Differential Scanning Calorimetry studies confirmed no drug-polymer interaction. Scanning Electron Microscopy images showcased uniform spherical nano-sized particles. Stability studies indicated no significant changes after 1 mo. The Cmax increased 4.35-fold (p<0.01), and AUC0-t enhanced 8.13-fold (p<0.001) compared to plain IBR with statistical significance. Conclusion: Results indicate that IBR-loaded PLGA NBs could be effective in sustaining its release for a prolonged period for the treatment of breast cancer. Targeted medicine delivery through passive targeting via enhanced permeability and retention is made possible by the potential use of NBs in the creation of ultrasonic-responsive combinations.